КЛАСТЕР МЕН ТЕРРИТОРИАЛДЫ-ӨНДІРІСТІК КЕШЕН ҰҒЫМДАРЫНЫҢ ЕРЕКШЕЛІКТЕРІ. - Тажиева, С. Қ. (Journal of Economic Research & Business Administration, 2016)
In this article analyzed cluster’s theory, comme the importance factor of the development of the competitiveness of the national economics.